Automated support for reuse‐based requirements engineering in global software engineering. Issue 8 (3rd May 2017) - Carrillo de Gea, Juan Manuel; Nicolás, Joaquín; Fernández‐Alemán, José L.; Toval, Ambrosio
Abstract : GlobalSoftware Engineering implies a paradigm shift towards globally‐distributed development that can be advantageous, but at the cost of having to address the specific challenges that arise when the stakeholders are not colocated. Reusing assets during the initial processes of the software development life cycle could be beneficial, but automated support is essential if the expected benefits of requirements reuse are to be actually obtained. The main contribution of this paper is the specification of a collection of software features for a tool support for distributed, catalogue‐based natural‐language requirements reuse. Two additional contributions are also made: (1) an implementation of the requirements specifications previously mentioned using Drupal, a Content Management System; and (2) an empirical assessment of this tool support using distributed university students as subjects ( n =57). According to our findings, the tool helps in making requirements reuse better than requirements specification from scratch and in managing traceability, is easy to use, useful, and easy to learn. In contrast, the tool is not particularly suitable for managing users and user roles.